Anti-pancreatic tumor efficacy of a Listeria-based, Annexin A2-targeting immunotherapy in combination with anti-PD-1 antibodies. Issue 1 (22nd May 2019) - Kim, Victoria M.; Blair, Alex B.; Lauer, Peter; Foley, Kelly; Che, Xu; Soares, Kevin; Xia, Tao; Muth, Stephen T.; Kleponis, Jennifer; Armstrong, Todd D.; Wolfgang, Christopher L.; Jaffee, Elizabeth M.; et al.
Abstract : Background: Immune checkpoint inhibitors are not effective for pancreatic ductal adenocarcinoma (PDAC) as single agents. Vaccine therapy may sensitize PDACs to checkpoint inhibitor treatments. Annexin A2 (ANXA2) is a pro-metastasis protein, previously identified as a relevant PDAC antigen that is expressed by a GM-CSF-secreting allogenic whole pancreatic tumor cell vaccine (GVAX) to induce an anti-ANXA2 antibody response in patients with PDAC. We hypothesized that an ANXA2-targeting vaccine approach not only provokes an immune response but also mounts anti-tumor effects. Methods: We developed a Listeria-based, ANXA2-targeting cancer immunotherapy (Lm-ANXA2) and investigated its effectiveness within two murine models of PDAC. Results: We show that Lm-ANXA2 prolonged the survival in a transplant model of mouse PDACs. More importantly, priming with the Lm-ANXA2 treatment prior to administration of anti-PD-1 antibodies increased cure rates in the implanted PDAC model and resulted in objective tumor responses and prolonged survival in the genetically engineered spontaneous PDAC model. In tumors treated with Lm-ANXA2 followed by anti-PD-1 antibody, the T cells specific to ANXA2 had significantly increased INFγ expression. Conclusions: For the first time, a listeria vaccine-based immunotherapy was shown to be able to induce a tumor antigen-specific T cell response within the tumor microenvironment of a "cold" tumor such as PDAC and sensitize the tumor to checkpoint inhibitor therapy. Moreover, this combination immunotherapy led to objective tumor responses and survival benefit in the mice with spontaneously developed PDAC tumors. Therefore, our study supports developing Lm-ANXA2 as a therapeutic agent in combination with anti-PD-1 antibody for PDAC treatment.